PENGARUH PEMAHAMAN SIGAT TAKLIK ‎TERHADAP PENELANTARAN HAK-HAK ‎ISTRI DI SENDANG SARI - Siregar, Mhd. Syafii Arozaq Siregar (Jurnal Ushuluddin, 2022)
In Islamic Law (KHI) and Law No. 1 of 1974, regulations concerning divorce agreements and marriage contracts are outlined. This study was prompted by a case in Sendang Sari Village where a wife did not assert her rights under the sighat taklik talak, due to being abandoned by her husband for several years, leading to his failure in providing the necessary support. The non-utilization of the wife's rights can potentially result in ambiguous marital status whether the marriage remains valid under the law or could be deemed dissolved automatically due to prolonged absence of the husband. Additionally, perceptions vary among residents of Sendang Sari Village regarding the significance of the sighat taklik talak after the marriage ceremony. Some view it as crucial while others do not. The research problem focuses on two main aspects: firstly, how Islamic Law examines the legal implications of unused rights by the wife resulting from taklik talak violations; secondly, Islamic Law's assessment of public perceptions towards taklik talak in Sendang Sari Village, West Kisaran District, Asahan Regency. This study aims to provide deeper insights into the legal implications of taklik talak and its societal relevance in local Indonesian contexts.